2019
DOI: 10.1097/ico.0000000000002217
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian Gland Dysfunction in a Hospital-Based Population in Central India

Abstract: Purpose: To estimate the prevalence of meibomian gland dysfunction (MGD) in a hospital-based population in India. Methods: This cross-sectional study screened 3410 subjects ≥20 years or older attending the outpatient department by systematic random sampling. The patients were subjected to a comprehensive eye examination, Ocular Surface Disease Index questionnaire, fluorescein tear film breakup time, Schirmer I test, lissamine green stain, lid margin cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…13,14 Therefore, it can be expected that older individuals will have a higher prevalence rate of MGD. 15 Due to the limited age range and small number of male subjects in our study, we were unable to compare the prevalence of MGD between age and gender. Since MGD is a very common eye disorder, an objective diagnostic tool is extremely helpful for ophthalmic healthcare workers to allow patients to visualize the severity of MGD and to individualize the treatment strategy.…”
Section: Discussionmentioning
confidence: 93%
“…13,14 Therefore, it can be expected that older individuals will have a higher prevalence rate of MGD. 15 Due to the limited age range and small number of male subjects in our study, we were unable to compare the prevalence of MGD between age and gender. Since MGD is a very common eye disorder, an objective diagnostic tool is extremely helpful for ophthalmic healthcare workers to allow patients to visualize the severity of MGD and to individualize the treatment strategy.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study on meibomian gland dysfunction, we observed fewer symptoms among elderly patients, even though there was a greater amount of lid margin changes in them. [ 26 ] Symptom perceptions in elderly subjects may be less due to changes in corneal nerve morphology and reduction in ocular surface sensitivity with increasing age. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence shows that the prevalence of MGD ranges from 3.5% to almost 70% in various countries, [ 1 ] and the data reported in Asian countries are generally higher than those reported in Western countries. [ 2 ] It is well established that MGD can not only cause ocular surface discomfort related to impaired meibomian gland (MG) function, but also give rise to intractable evaporative dry eye. [ 3 ] However, consensus regarding the optimal intervention strategy is lacking.…”
Section: Introductionmentioning
confidence: 99%